2004
DOI: 10.1126/science.1097468
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Glutamate Transporters 1 and 2 Target to Functionally Distinct Synaptic Release Sites

Abstract: Vesicular glutamate transporters (VGLUTs) 1 and 2 show a mutually exclusive distribution in the adult brain that suggests specialization for synapses with different properties of release. Consistent with this distribution, inactivation of the VGLUT1 gene silenced a subset of excitatory neurons in the adult. However, the same cell populations exhibited VGLUT1-independent transmission early in life. Developing hippocampal neurons transiently coexpressed VGLUT2 and VGLUT1 at distinct synaptic sites with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
459
8
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(521 citation statements)
references
References 27 publications
45
459
8
9
Order By: Relevance
“…Previous studies show that VGLUT1 is the major isoform in both the frontal cortex and the hippocampus (30,31), where it plays a key role in the vesicular uptake and synaptic transmission of glutamate (13)(14)(15)(16). The downregulation of cortical and hippocampal EAAT1 supports the idea of decreased glutamate release in the VGLUT1 dependent synapses because this glial transporter is regulated by the amount of glutamate released into the synaptic cleft (32,33).…”
Section: Regulation Of Glutamate/gaba Cycle and Behaviour By Reduced supporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies show that VGLUT1 is the major isoform in both the frontal cortex and the hippocampus (30,31), where it plays a key role in the vesicular uptake and synaptic transmission of glutamate (13)(14)(15)(16). The downregulation of cortical and hippocampal EAAT1 supports the idea of decreased glutamate release in the VGLUT1 dependent synapses because this glial transporter is regulated by the amount of glutamate released into the synaptic cleft (32,33).…”
Section: Regulation Of Glutamate/gaba Cycle and Behaviour By Reduced supporting
confidence: 58%
“…At the experimental level, the vesicular glutamate transporter 1 (VGLUT1) has been reported to play a key role in the synaptic release (12) and the efficacy of glutamatergic synaptic transmission (13)(14)(15)(16). A recent study carried out in our laboratory reports that mice heterozygous for VGLUT1 (VGLUT1+/-), exhibit decreased cortical and hippocampal levels (35-45 %) of the inhibitory neurotransmitter GABA as well as helplessness in the forced swimming test (17).…”
Section: Introductionmentioning
confidence: 99%
“…(Adult) Purkinje cells do express glycine receptors (Triller et al 1987), though these are rather sparsely localized on main dendritic shafts. It is presently not clear whether the failure to detect glycinergic input into Purkinje cells by Lugaro cells relates to the developmental expression of glycinergic receptors by Purkinje cells, or rather reXects diVerential loading of Lugaro cell vesicles targeted to Lugaro/Golgi and Lugaro/Purkinje cell synapses, respectively (for a model, cf Fremeau et al 2004;Schuske and Jorgensen 2004). As the vesicular transporter VGAT/VIAAT is nonselective for GABA or glycine (which compete for it; Chaudhry et al 1998;Wojcik et al 2006), such a scenario would imply diVerential sorting and/ or membrane availability of membrane transporters for glycine and GABA.…”
Section: Large Inhibitory Interneurons Of the Granule Cell Layermentioning
confidence: 99%
“…To further characterize the development of the synaptic complexes in the IPB, we analyzed the synaptic complexes for the presence of presynaptic and postsynaptic molecular markers (presynaptic, VGLUT1 and VGLUT2; postsynaptic, NMDAR1) (Malenka and Nicoll, 1993;Petralia et al, 1994;Nicoll and Malenka, 1995;Fremeau et al, 2001Fremeau et al, , 2004a. Unexpectedly, we found that VGLUT1 and VGLUT2 were both expressed in the developing mossy fibers (as observed in the MB at P15) (Fig.…”
Section: Synaptic Complexes That Are Formed In the Ipb Before Pruningmentioning
confidence: 99%